Development Of Shoe Dryer System Using Microcontroller With GSM Module - Abd Mutalib, Nurliyana; Johari, Siti Halma; Abdul Hadi, Dayanasari; Ahmad, Suziana; Hamzah, Rostam Affendi; Arumugam, Navine; Zahari, Madiha; Ab Wahab, Norfariza (Penerbit UTHM, 2019)
This paper describes the design and development of a shoe dryer using a microcontroller. Nowadays, people often travel and sometimes in rainy day, they need to dry their shoe in a very short time anywhere. However, very rare of places including shopping mall and hotel provide a shoe dryer. The shoe dryer is designed to help people who are in hurry to dry their shoe on the go. A temperature sensor is used to measure the temperature inside the shoe dryer, while a program is uploaded in the microcontroller for reading and data collection. The programming includes the activation of shoe dryer with the GSM module, thus it can be controlled using a mobile phone. An experiment was conducted to test the performance of the shoe dryer. The optimum performance was obtained when the temperature is set at 36°C, and timer at 60 seconds with normal room temperature. The temperature and timer need to be adjusted accordingly based on the shoe condition in order to get very satisfying results. This paper proved that the shoe dryer was successfully designed, implemented and analyzed.